Less Midterm Damage and Oxidation Are Seen in Retrieved Highly Crosslinked Ultrahigh-Molecular-Weight Polyethylene Tibial Inserts than in Direct Compression Molded Polyethylene Inserts. Issue 2 (July 2018) - Stavrakis, Alexandra; Weitzler, Lydia; Wright, Timothy; Padgett, Douglas E.
Background: Highly crosslinked ultrahigh-molecular-weight polyethylene (XLPE) shows reduced wear in total hip arthroplasty compared to direct compression-molded polyethylene (compPE); however, minimal research evaluating polyethylene damage in XLPE tibial inserts in total knee arthroplasty exists. Questions/Purposes: We evaluated damage and material properties in retrieved XLPE components at midterm (≥ 2.5 years) follow-up. Methods: We identified 19 XLPE tibial inserts with ≥ 30 months in vivo using our institutional review board–approved implant retrieval system; 19 compPE retrieved inserts were matched based on age at index surgery, body mass index, sex, and length of implantation. Articular surface damage was assessed using a subjective grading system. Swell ratio testing and Fourier-transform infrared spectroscopy were used to measure crosslink density (XLPE) and oxidation (XLPE, compPE), respectively, at loaded and unloaded surface and subsurface regions. Results: CompPE inserts had higher overall damage than XLPE inserts, specifically at the post of posterior-stabilized inserts. The XLPE inserts had lower crosslink density at the loaded surface (0.159 mol/dm 3 ) than either unloaded region (0.183 mol/dm 3 ). CompPE peak oxidation index (OI) was greater than XLPE peak OI in the loaded and unloaded surface regions (1.67 vs. 0.61 and 1.38 vs. 0.46, respectively). Conclusions: Surface damage and oxidation are reduced in XLPE inserts compared to compPE at midterm follow-up. Peak OI greater than 1.0 in the compPE group suggests that mechanical-property degradation had occurred, a likely cause for increased damage. Longer-term retrievals will determine whether these trends continue. Based on midterm results, XLPE shows an advantage over compression molded PE in total knee arthroplasty.